(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents considerations on the development of students’ creative abilities through the Arduino platform. It was shown that using this platform in the teaching process increased students’ creativity, creative abilities, and the level of knowledge acquisition increased by 20-30%. The functional capabilities of Smart and Stem, Khoot methods were shown as ways to reveal creative abilities.